The Implementation of Ecosystem Urban Farming Program (BRInita) in Kampung Bali, Central Jakarta as Community Development by PT Bank Rakyat Indonesia for Food Security and Environmental Sustainability - Tri Apriansyah; Ety Rahayu (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The rapid growth of urban populations globally has resulted in the conversion of agricultural land into urban settlements, posing significant threats to food security. The BRInita program, implemented by PT Bank Rakyat Indonesia (BRI), aims to address these issues through urban farming in densely populated areas. This study examines the implementation of the BRInita program in Kampung Bali, Central Jakarta, during 2023. Utilizing a qualitative research approach, this study highlights the program's contributions to community development, environmental sustainability, and food security. The results demonstrate significant hydroponic yields and successful establishment of urban farming practices, indicating the program's potential as a model for similar urban areas.